THE EFFECT OF THE JIGSAW TYPE COOPERATIVE LEARNING MODEL ON IMPROVING STUDENTS' AFFECTIVE LEARNING OUTCOMES HKBP PRIVATE VOCATIONAL SCHOOL PEMATANGSIANTAR - Bangun Munthe; Imelda Butarbutar; Justinos Ray Nainggolan; Josua Manurung; Yuliana Simbolon (RADJA PUBLIKA, 2026)
This study aims to determine whether there is (1) an increase in student learning outcomes using the jigsaw cooperative learning model. The study was conducted in two cycles with each cycle consisting of planning, action implementation, observation and reflection. The subjects of this study were 20 students of class XII of SMK Swadaya HKBP Pematangsiantar in the 2025/2026 academic year. The data sources used were informants, places or locations, events, documents or archives. Data collection techniques were carried out by observation, interviews, tests, questionnaires and documentation. Data validity used source triangulation techniques. Data analysis used qualitative descriptive analysis techniques. The results of the study showed that the religious learning outcomes of class XII students of SMK Swadaya HKBP Pematangsiantar experienced an increase after the implementation of the Jigsaw cooperative learning model. The method used in this study is an experiment, with a one group pretest-posttest design used to determine the effect of a treatment on the research subjects. The population of this study was class XII at SMK Swasta HKBP Pematangsiantar, with samples of class XII-TKJ and XII-KKY. The research data were obtained using a multiple-choice instrument of 20 questions and a pretest was conducted before learning and a posttest after learning. From the results of the study, an average pretest of 64.15 and a posttest of 92.5 was obtained. From the results of the hypothesis test, t_count > t_table at a significance level of 5% or 0.05, namely (4.49 > 1.70). Based on the results of the data analysis obtained, it can be concluded that learning with the jigsaw type cooperative learning model can improve student learning outcomes as seen from the increase in pretest and posttest scores.